Sistema de informação de custos: um estudo nos estados brasileiros - Silva, Angeliana Ferreira da (2024)
In the brazilian public sector, the use of cost information dates back to the publication of law nº 4.320/1964. With the aim of improving accounting practices in the Brazilian public sector, the Federal Accounting Council (CFC) published in 2021 NBC TSP nº 34 - Costs in the Public Sector, which must be applied from 01/01/2024, and establishes guidelines and standards for the implementation of the cost information system (SIC) in the public sector. Thus, the present research has the general objective of investigating the process of implementing the SIC in the Brazilian states and the Distrito Federal, from the perspective of NBC TSP 34. Therefore, descriptive field research of a qualitative and quantitative was carried out, using a structured questionnaire. The analysis of the collected data was carried out using descriptive statistics using electronic spreadsheets.The results point to the main factors for the high difficulty in implementing the SIC: non-exclusive team to work on the cost project (accumulation of activities), insufficient number of technical team members, and lack of integration of internal structuring systems. Regarding the expected benefits of implementing the SIC, it was verified: a higher level of agreement related to increased public transparency, subsidies to improve decision-making by managers and the presentation of the costs of public services made available to users. The results obtained indicate that 66.7% of the sample is in the study phase related to the SIC, but has not yet started implementation, and 25% have an implemented system, but in the improvement phase (pilot test). The study shows that perceptions about the difficulties in implementing a SIC in the public sector are related to concrete aspects , while the benefits are abstract and need to be better detailed and publicized, so that this implementation has occurred slowly, considering the edition of NBC T 16.11 in 2011. Therefore, as long as there is no prioritization by senior public management in relation to effective knowledge and development of the cost system, the topic will probably remain the subject of deadline extensions. It is therefore suggested that the SIC be a state policy, supported by the Federal Government as Central Government, taking into account the particularities, similarities and differences of each Brazilian State.